A Historical Overview of The Most Successful Tax Amnesty Policies in Indonesia - Wardana, Arief Budi (Magister Ilmu Administrasi Publik, 2024)
The 2016 Tax Amnesty may be the most successful tax amnesty program in Indonesia. However, the debate on introducing the Voluntary Disclosure Program in 2022 raises questions. The purpose of this research is to examine the experiences of informants during the discussion and drafting of the 2016 Tax Amnesty from the aspects of background, timing, design, and accompanying strategies. A narrative qualitative approach using interview instruments is suitable for achieving the research objectives. Based on what the informants experienced, the 2016 Tax Amnesty emerged from the need to increase tax revenues to support the implementation of government programs. In addition, essential aspects such as time and design were considered when discussing the 2016 Tax Amnesty. However, another critical aspect was overlooked, namely the accompanying strategy of the tax amnesty.